Sharing a Context with Other Rewarding Events Increases the Probability that Neutral Events will be Recollected - Loh, Eleanor; Deacon, Matthew; de Boer, Lieke; Dolan, Raymond J.; Duzel, Emrah (Frontiers in Human Neuroscience, 2016)
Although reward is known to enhance memory for reward-predicting events, the extent to which such memory effects spread to associated (neutral) events is unclear. Using a between-subject design, we examined how sharing a background context with rewarding events influenced memory for motivationally neutral events (tested after a five day delay). We found that sharing a visually rich context with rewarding objects during encoding increased the probability that neutral objects would be successfully recollected during memory test, as opposed to merely being recognized without any recall of associative detail. In contrast, such an effect was not seen when the context was not explicitly demarcated and objects were presented against a blank black background. These qualitative changes in memory were observed in the absence of any effects on overall recognition (as measured by d’). Additionally, a follow-up study failed to find any evidence to suggest that the mere presence of a context picture in the background during encoding (i.e. without the reward manipulation) produced any such qualitative changes in memory. These results suggest that reward enhances recollection for rewarding objects as well as other non-rewarding events that are representationally linked to the same context.